Investigação de elementos de transposição em populações de Drosophila mojavensis e D. arizonae e seus híbridos - Carnelossi, Elias Alberto Gutierrez [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This thesis aimed to investigate how transposable elements (TEs), sequences capable of moving into the host genome and between different species, behave in interspecific hybrids. We seek to understand the activity of TEs in crosses between Drosophila mojavensis and D. arizonae due to some particular characteristics of this species pair. They are sister species, with very recent divergence ( < 1 million years ), present incomplete pre- and post- zygotic reproductive isolation in laboratory and one of them, D. mojavensis, had its genome sequenced, which allowed for in silico analyses of TEs. The thesis is divided into four chapters. The first presents a detailed analysis of an non- LTR retrotransposon called I, known to cause hybrid dysgenesis in D. melanogaster. Putatively active sequences similar to the I element were identified and characterized in the genome of D. mojavensis. The performed phylogenetic analyzes showed that the I sequences in D. mojavensis and those harbored by other Drosophila species belong to different I families. Expression analyses by RTq-PCR showed that this element is transcriptionally active in ovaries and testes of both species and their hybrids, and have high expression in the testes, but not in the hybrids ovaries, which could be associated with the male hybrid sterility phenotype. In the second chapter are presented analyses of expressed TEs in the ovaries of two parental strains and their hybrids by RNA-Seq. The results show species-specific expression of TEs in the parents and hybrids; and, in an unprecedented manner, that TEs are generally regulated in hybrids regarding with their parents, although some of them are overexpressed. In the third chapter are presented results of expression of four retrotransposons (Helena , I, Copia and Osvaldo) quantified by RTq-PCR; and finally, in the last chapter, we presented estimates of the genome size ( C - value), in both parental species and reciprocal hybrids ...

Essa tese teve como principal objetivo investigar como os elementos de transposição (TEs), sequências capazes de se movimentarem no genoma hospedeiro, e entre diferentes espécies, se comportam em híbridos interespecíficos. Buscou-se compreender a atividade do TEs em cruzamentos entre Drosophila mojavensis e D. arizonae devido a algumas características particulares desse par de espécies. São espécies irmãs, com divergência muito recente (< 1 milhão de anos), apresentam isolamento reprodutivo pré- e pós-zigótico incompleto em laboratório e uma delas, D. mojavensis, teve seu genoma sequenciado, o que permitiu a realização de análises in silico de TEs dessa espécie. A tese foi dividida em quatro capítulos. O primeiro apresenta uma análise detalhada do retrotransposon NLTR denominado I, conhecido por causar disgenesia híbrida em D. melanogaster. Foram identificadas e caracterizadas sequências putativamente ativas de elementos semelhantes ao I no genoma de D. mojavensis e realizadas análises filogenéticas que mostraram que as sequências I de D. mojavensis e aquelas encontradas em outras espécies de Drosophila pertencem a diferentes famílias I. Análises de expressão por RTq-PCR mostraram que esse elemento é transcricionalmente ativo nos ovários e testículos de ambas as espécies, e em seus híbridos, e que têm elevada expressão em testículos, mas não em ovários dos híbridos, o que poderia ser associado ao fenótipo de esterilidade do macho hibrido. No segundo capítulo são apresentadas análises por RNA-Seq de TEs expressos em ovários de duas linhagens parentais e seus híbridos F1. Os resultados mostram expressão espécie-específica de diferentes elementos nas espécies parentais e híbridos; e, de forma inédita, que apesar de alguns TEs estarem superexpressos nos híbridos, encontram-se de forma geral regulados em relação aos parentais. No terceiro capítulo são apresentados resultados de expressão ...
Activity of transposable elements in populations of Drosophila mojavensis and D. arizonae and in their hybrids
Keywords: Genetica molecular; Hibridação; Drosófila - Genética; Drosófila mojavensis; Drosófila arizonensis; Elementos genéticos móveis; Molecular genetics